Counter-examples to an Assertion Concerning the Normal Distribution and a New Stochastic Price Fluctuation Model - Agnew, R. A. (Review of Economic Studies, 1971)
Journal Article Counter-examples to an Assertion concerning the Normal Distribution and a New Stochastic Price Fluctuation Model Get access R. A. Agnew R. A. Agnew Air Force Institute of Technology Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 38, Issue 3, July 1971, Pages 381–383, https://doi.org/10.2307/2296391 Published: 01 July 1971